2017
DOI: 10.1103/physrevmaterials.1.075601
|View full text |Cite
|
Sign up to set email alerts
|

Electronic band gaps of confined linear carbon chains ranging from polyyne to carbyne

Abstract: Ultra long linear carbon chains of more than 6000 carbon atoms have recently been synthesized within doublewalled carbon nanotubes, and they show a promising new route to one-atom-wide semiconductors with a direct band gap. Theoretical studies predicted that this band gap can be tuned by the length of the chains, the end groups, and their interactions with the environment. However, different density functionals lead to very different values of the band gap of infinitely long carbyne. In this work, we applied r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
122
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(142 citation statements)
references
References 42 publications
11
122
0
9
Order By: Relevance
“…Inner nanotubes in DWCNTs and MWCNTs are suggested to serve as templates in the formation of LCC . Very recently, effects of the inner tube diameter on vibration and electronic properties of encapsulated LLCs are studied carefully . In the present study, by transmission electron microscopy (TEM) and Raman spectroscopy, we found the presence of a bulk amount of LCCs in CNT films after an electric discharge of the films that were used as a cathode of field emission (FE).…”
Section: Introductionsupporting
confidence: 76%
“…Inner nanotubes in DWCNTs and MWCNTs are suggested to serve as templates in the formation of LCC . Very recently, effects of the inner tube diameter on vibration and electronic properties of encapsulated LLCs are studied carefully . In the present study, by transmission electron microscopy (TEM) and Raman spectroscopy, we found the presence of a bulk amount of LCCs in CNT films after an electric discharge of the films that were used as a cathode of field emission (FE).…”
Section: Introductionsupporting
confidence: 76%
“…It is has been reported that the interaction between the outer and inner tubes could shift the RBM of inner tubes by 30 cm −1 at the maximum. 41,42 In our case, the frequency-shifts of the extracted (6,4) and (6,5) chirality tubes compared to those inside DWCNTs are both within 1 cm −1 (Fig.1c and Figs.5c and 5d), suggesting that the effect of the outer tubes is comparable to the one from the surrounding IO/surfactants as well as the LCC in total. This effect resembles that of bundling regarding energy space increments and broadening of the van Hove singularities of the bundled tubes, explaining the shifts in the RBM frequencies.…”
Section: Resultssupporting
confidence: 60%
“…Furthermore, the Raman spectra shown in Fig.1c illustrate the difference between the two separated parts and confirm the successful extraction again. From these spectra (6,4) and (6,5) tube chiralities can be clearly identified in the low-frequency radial breathing mode (RBM) region for the top layer, [33][34][35] whereas much more signal from both the inner and outer tubes of DWCNTs can be seen in the bottom region sample. Note that the peak labelled IO conresponding to the signal arising from the iodixanol density gradient medium (see supplementary Fig.S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations